(untitled) (American International Journal of Business and Management Studies, 2020)
The impact of monetary policies and their implementation by the exchange rate covered the economic condition of Ghana. The social inclusion and conversion factors change the implemented policies of nations, where the real price, trade, technology, a price rate, and price level of ratio take an important part of growth. The reform of the financial sector favors the free-floating of the exchange rate and global trade under the premise of flexible exchange rates. The tragedy of country growth and exchange rate toward a trajectory of growth with the growth-enhancing effect through social inclusion, conversion factors, price level ratio, exchange rate, merchant rate, export, and trade services. The research study is based on the secondary study and social inclusion equity indicators with public resources, building human resources and social protection for economic development has determined. Different evidence and trade indicators classify the monetary policies. The significant influence of growth and internal policies has affected trade and exchange rates with growth and reserve policies. The results have computed by linear regression and it proved that social inclusion and alternative conversion factors impact on global trade and create short term binary relationships.